How Do Children Deal With Conflict? A Developmental Study of Sequential Conflict Modulation - Smulders, Silvan F. A.; Soetens, Eric L. L.; van der Molen, Maurits W. (Frontiers in Psychology, 2018)
This study examined age-related differences in sequential conflict modulation, elicited in three tasks requiring the inhibition of prepotent responses; a Simon task, an S-R compatibility (SRC) task and a hybrid Choice-reaction/NoGo task. The primary focus was on age-related changes in performance changes following a conflict trial. A secondary aim was to assess whether sequential conflict modulation follows different developmental trajectories depending on the type of conflict elicited by the tasks. The tasks were presented to three different groups of participants with an age range between 7 to 25 years—one group of participants for each task. For each task, the response-to-stimulus interval (RSI) was manipulated (50 vs. 500 ms) across trial blocks to assess time-dependent changes in conflict modulation. The results showed sequential conflict modulation for all three tasks, although the specific patterns differed between tasks and RSIs. Importantly, the magnitude of sequential conflict modulation decreased with advancing age, but this developmental trend did not survive when considering age-group differences in basic response speed. The current results contribute to the emerging evidence suggesting that patterns of sequential conflict modulation are task specific and were interpreted in terms of multiple bottom-up control mechanisms.